Oxidative and Glycation Damage to Mitochondrial DNA and Plastid DNA during Plant Development - Diwaker Tripathi; Delene J. Oldenburg; Arnold J. Bendich (MDPI AG, 2023)
Oxidative damage to plant proteins, lipids, and DNA caused by reactive oxygen species (ROS) has long been studied. The damaging effects of reactive carbonyl groups (glycation damage) to plant proteins and lipids have also been extensively studied, but only recently has glycation damage to the DNA in plant mitochondria and plastids been reported. Here, we review data on organellar DNA maintenance after damage from ROS and glycation. Our focus is maize, where tissues representing the entire range of leaf development are readily obtained, from slow-growing cells in the basal meristem, containing immature organelles with pristine DNA, to fast-growing leaf cells, containing mature organelles with highly-fragmented DNA. The relative contributions to DNA damage from oxidation and glycation are not known. However, the changing patterns of damage and damage-defense during leaf development indicate tight coordination of responses to oxidation and glycation events. Future efforts should be directed at the mechanism by which this coordination is achieved.